EU Sanctions Policy in the Sino-European Relations - Petrová, Eliška; Stuchlíková, Zuzana, 1979-; Lehmannová, Zuzana, 1951-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2017)
The main objective of this thesis is to assess whether the arms embargo from 1989 removal is an option for the European Union. The paper is divided into two major chapters. The first chapter introduces the theoretical framework of EU sanction policy and restrictive measures. Also, the timeline and reasons for the embargo imposition are described. The second one examines Sino-European relations in terms of political discourse and especially arms trade because both are connected with the topic of the arms embargo. The approaches towards the embargo of all actors are also discussed.
Vedoucí práce: Zuzana Stuchlíková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: mezinárodní politika a diplomacie [obor dipl. práce]; diplomové práce; master's theses